Sarita Colonia: estetización del ícono y uso de imágenes ¿para la autonomía cultural? - Hernandez Lefranc, Harold (2007)
Thepresent text proposes that the popularity and worship of Sarita Colonia has been possible thanks to the media and to intellectual uthopic or disruptive motivations opposed to the bourgeois society. Jt also asks why did Sarita Colonia undergoa post mortemplastic surgeryfrom an Andean phenotype to a caucasian one? The answer is that this surgery applies to both her iconography and her discourse. The author wonders if it is possible to speak about cultural autonomy of the urban populace, when it only accepts those icons that are «whitened». He a/so states that this practice of whitening of icons inpaintings and photographs extends to other saints and exceeds the religious space